Pharmacokinetic and Pharmacodynamic Properties of Cemdisiran, an RNAi Therapeutic Targeting Complement Component 5, in Healthy Subjects and Patients with Paroxysmal Nocturnal Hemoglobinuria - Badri, Prajakta; Jiang, Xuemin; Borodovsky, Anna; Najafian, Nader; Kim, Jae; Clausen, Valerie A.; Goel, Varun; Habtemariam, Bahru; Robbie, Gabriel J. (Clinical pharmacokinetics, 2021)
Background Cemdisiran, an N -acetylgalactosamine (GalNAc) conjugated RNA interference (RNAi) therapeutic, is currently under development for the treatment of complement-mediated diseases by suppressing liver production of complement 5 (C5) protein. This study was designed to evaluate the safety, tolerability, pharmacokinetics (PK), and pharmacodynamics (PD) of cemdisiran in healthy subjects and in patients with paroxysmal nocturnal hemoglobinuria (PNH) in order to support dose selection for late-stage clinical trials. Methods Healthy volunteers (HVs; n = 32, including 12 Japanese subjects) were randomized (3:1) to receive single doses of subcutaneous cemdisiran (50–900 mg) or placebo, or repeat doses of subcutaneous cemdisiran (100–600 mg) or placebo weekly, biweekly, weekly/biweekly, or weekly/monthly for 5, 8, or 13 weeks ( n = 24). Cemdisiran 200 or 400 mg was administered weekly in an open-label manner, for varying durations, as monotherapy in three eculizumab-naïve PNH patients or in combination with eculizumab in three PNH patients who were receiving stable label doses of eculizumab (900 or 1200 mg biweekly) before the start of the study. After the last dose of cemdisiran, patients were followed for safety and ongoing pharmacologic effects with the eculizumab regimen (600 or 900 mg every month). Results In HVs, cemdisiran was rapidly converted to a major active metabolite, AS(N-2)3′-cemdisiran, both declining below the lower limit of quantification (LLOQ) in plasma within 48 h, and showing minimal renal excretion. AS(N-2)3′-cemdisiran exhibited more than dose-proportional PK. The C5 protein reductions were dose-dependent, with > 90% reduction of C5 protein beginning on days 21–28 and maintained for 10–13 months following single and biweekly doses of 600 mg. The dose–response relationship, described by an inhibitory sigmoid maximum effect ( E max ) model, estimated half-maximal effective dose (ED 50 ) of 14.0 mg and maximum C5 reduction of 99% at 600 mg. The PK and PD were similar between Japanese and non-Japanese subjects, and PNH patients and HVs. One of 48 subjects tested transiently positive for antidrug antibody with low titer, with no impact on PK or PD. In PNH patients, C5 suppression by cemdisiran enabled effective inhibition of residual C5 levels with lower dose and/or dosing frequency of eculizumab, which was maintained for 6–10 months after the last dose of cemdisiran. Conclusions Consistent with the PK/PD properties of liver targeting GalNac conjugates, cemdisiran and AS(N-2)3′-cemdisiran plasma concentrations declined rapidly while showing rapid and robust C5 suppression maintained up to 13 months following single and multiple doses, which indicates long residence times of cemdisiran within hepatocytes. The long PD duration of action in liver, low immunogenicity and acceptable safety profiles enables low, infrequent SC dosing and support further evaluation of cemdisiran in complement-mediated diseases as monotherapy or in combination with a C5 inhibitor antibody. Clinical Trial Registration No NCT02352493.